Headache in three new cases of Harlequin syndrome with accompanying pharmacological comparison with migraine. Issue 6 (6th April 2012) - Viana, Michele; Mathias, C J; Goadsby, Peter J
Abstract : Background: Harlequin syndrome (HS) is a rare autonomic disorder characterised by unilateral diminished sweating and flushing of the face in response to heat or exercise. Some patients with HS complain of headache. Methods: We present three new cases to characterise their headache phenotype and pharmacology and review the literature of cases where headache was described. Results: Two out of the three patients presented with episodes of unilateral headache associated with exercise: in one case the headache had migrainous features and was contralateral to the side where the flushing occurred, whereas the second patient, who had had migraine attacks in the past, had a brief throbbing headache, with no associated symptoms, ipsilateral to the facial flushing. The third woman had migraine but the attacks were not associated with HS. Pharmacological characterisation suggested the HS and migraine were biologically distinct. HS was not triggered by nitroglycerin and was unaffected by sumatriptan, dihydroergotamine and ergotamine. HS and migraine did not occur together. In the literature, we found six patients with both HS and headache, five of whom had migraine. Conclusions: These data do not show any correlation between the phenotypic expression of migraine and HS suggesting the syndromes are pathogenetically independent.